Autopsy-diagnosed neurodegenerative dementia cases support the use of cerebrospinal fluid protein biomarkers in the diagnostic work-up - Bruzova, Magdalena; Rusina, Robert; Stejskalova, Zuzana; Matej, Radoslav (Scientific reports, 2021)
Various proteins play a decisive role in the pathology of different neurodegenerative diseases. Nonetheless, most of these proteins can only be detected during a neuropathological assessment, although some non-specific biomarkers are routinely tested for in the cerebrospinal fluid (CSF) as a part of the differential diagnosis of dementia. In antemortem CSF samples from 117 patients with different types of neuropathologically confirmed neurodegenerative disease with dementia, we assessed total-tau (t-tau), phosphorylated-tau (181P) (p-tau), amyloid-beta (1-42) (Aβ42), TAR DNA binding protein (TDP)-43, progranulin (PGRN), and neurofilament light (NfL) chain levels, and positivity of protein 14-3-3. We found t-tau levels and the t-tau/p-tau ratios were significantly higher in prion diseases compared to the other neurodegenerative diseases. Statistically significant differences in the t-tau/Aβ42 ratio predominantly corresponded to t-tau levels in prion diseases and Aβ42 levels in AD. TDP-43 levels were significantly lower in prion diseases. Additionally, the TDP-43/Aβ42 ratio was better able to distinguish Alzheimer's disease from other neurodegenerative diseases compared to using Aβ42 alone. In frontotemporal lobar degeneration, PRGN levels were significantly higher in comparison to other neurodegenerative diseases. There is an increasing need for biomarkers suitable for diagnostic workups for neurodegenerative diseases. It appears that adding TDP-43 and PGRN to the testing panel for neurodegenerative diseases could improve the resolution of differential diagnoses.
Keywords: Amyloid beta-Peptides; senioři nad 80 let; demence; proteiny v mozkomíšním moku; retrospektivní studie; Humans; diferenciální diagnóza; Cerebrospinal Fluid Proteins; lidé středního věku; Middle Aged; Aged, 80 and over; Autopsy; Neurofilament Proteins; regulace genové exprese; Sensitivity and Specificity; Gene Expression Regulation; Peptide Fragments; DNA-Binding Proteins; mužské pohlaví; neurofilamentové proteiny; proteiny tau; 14-3-3 Proteins; Diagnosis, Differential; Dementia; DNA vazebné proteiny; peptidové fragmenty; biologické markery; ženské pohlaví; tau Proteins; amyloidní beta-protein; pitva; lidé; senzitivita a specificita; progranuliny; Progranulins; Biomarkers; Aged; senioři; Male; Retrospective Studies; proteiny 14-3-3; Female